E and F are independent iff $\frac{p(E \cap F)}{p(F)}=p(E)$.

Also, E and F are independent iff $p(E | F)=p(E)$

Why do I get nonsense if I combine the two? I'd get: E and F are independent iff $p(E | F) = \frac{p(E \cap F)}{p(F)}$

Why doesn't the iff carry over when I combine the two equations?

  • 13
    $\begingroup$ Why would you expect that to work? $\endgroup$ – Eric Wofsey Mar 4 '18 at 6:28
  • 1
    $\begingroup$ @EricWofsey I consider iff to indicate equality, so I was intuitively expecting the "iff" to carry over and I'm not grasping why it isn't $\endgroup$ – JobHunter69 Mar 4 '18 at 6:29
  • $\begingroup$ You have combined illogically. What we do have is : $E, F $ are independent iff $p(E)=p(E|F)=p(E\cap F)/p(F).$.... For $any $ $ E $ we have $ p(E|F)=p(E\cap F)/p(F)$ so $E,F$ are independent iff $p(E) $ is equal to either of them. $\endgroup$ – DanielWainfleet Mar 5 '18 at 9:42

Let $a=\frac{p(E \cap F)}{p(F)}$, $b=p(E | F)$, and $c=p(E)$. You know that the equations $a=c$ and $b=c$ are equivalent to each other (since they are both equivalent to "$E$ and $F$ are independent"). That is, whenever $a=c$ is true, $b=c$ is also true, and conversely.

There is no reason for $a=b$ to be equivalent to these two statements, though. If $a=c$ is true, then $b=c$ is also true, and so $a=b$ is true as well. So we have an implication in one direction. But the other direction doesn't work: if we know $a=b$, that doesn't tell us anything about whether $a=c$ or $b=c$ are true. It's entirely possible that $a$ and $b$ are equal to each other, but not to $c$.

  • 2
    $\begingroup$ In fact, $a$ and $b$ in this case are equal to each other by definition, regardless of whether $E$ and $F$ are independent. $\endgroup$ – Bolton Bailey Mar 5 '18 at 3:48
  • $\begingroup$ What you did is equivalent to saying, "E and F are independent if E and F are independent." $\endgroup$ – richard1941 Mar 12 '18 at 15:37

You combined them wrong. From $A \Leftrightarrow B$ and $A \Leftrightarrow C$, you can infer $B \Leftrightarrow C$.

But you've misidentified what $A,B,C$ are. They aren't the sides of the equation, but rather

  • $A$ is the statement "$E$ and $F$ are independent"
  • $B$ is the formula $\frac{p(E \cap F)}{p(F)}=p(E)$
  • $C$ is the formula $p(E | F)=p(E)$

so the correct combination is

$$ \frac{p(E \cap F)}{p(F)}=p(E) \qquad \mathrm{iff} \qquad p(E | F)=p(E)$$


Here is a simple mathematical example to clearly elucidate the logical error:

An integer $n$ is an even prime iff $n = 2$.

An integer $n$ is an even prime iff $n = 1+1$.

(WRONG!) An integer $n$ is an even prime iff $2 = 1+1$.

  • 5
    $\begingroup$ I don't feel like this example is much different than my question, so it doesn't elucidate anything for me. $\endgroup$ – JobHunter69 Mar 5 '18 at 19:44

[This answer assumes the OP's argument is different from that assumed by the other answers.]

There's a logical fallacy in your argument, which seems to be of the following form:

  1. $A\iff(x=y)$
  2. $A\iff(z=y)$, where we define $z::=x$
  3. Hence, $A\iff [(x=y)\land (z=y)]$

So far, so good, but the next step, eliminating $y$ in the conjunction, is incorrect:

  1. Therefore, $A\iff(x=z)$.

That step would be correct if $$[(x=y)\land (z=y)]\ \ \iff\ \ (x=z), $$ but this fails simply because $$[(x=y)\land (z=y)]\require{cancel}\ \ \cancel\impliedby\ \ (x=z). $$

NB: In your case, $A$=("$E,F$ are independent"), $x=\frac{p(E \cap F)}{p(F)},$ $y=p(E),$ and $z=p(E\mid F).$


To address the more general question, here’s an example:

Suppose Kim Jong Un tells you, “In a democracy, what the leader promised is what the people voted for, and what the people voted for is what the government does. Just bear with me and take that as a definition. Therefore, I rule a democracy, because what the leader promised is what the government does.”


Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.